Innovation: The Attacker's AdvantageInnovation: The Attacker's Advantage, by FosterRichard. New York: Summit Books. 1986, 316 pp. $19.95, cloth. - Otto, Edwin R. (Academy of Management Review, 1987)
The article reviews the book ?Innovation: The Attacker's Advantage,? by Richard Foster.